1981
DOI: 10.2307/3280632
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Schistosoma mansoni In vitro. I. Establishment of Cultures from Cercariae and Development until Pairing

Abstract: Procedures are described for mass cultivation of Schistosoma mansoni. Cercariae were pooled, concentrated, and axenized through a series of washes in base medium containing antibiotics. Cercariae were sheared through a double-Luer-ended needle connected to two syringes, and tails separated and discarded. Young schistosomules were grown in a medium based upon BME augmented with lactalbumin hydrolysate, glucose, hormones, and other amendments and supplemented with human serum. Human blood cells (Type O) were add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
225
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(235 citation statements)
references
References 8 publications
9
225
0
1
Order By: Relevance
“…For the isolation of cercarial bodies from tails, an ice-cold Hank's basal salt solution (HBSS) is added to the cercarial suspension and the tail-rich supernatant is decanted (Manneck et al 2009). Schistosomula are incubated in Basch medium (Basch, 1981) supplemented with serum and antibiotics or other culture media (Smyth and Halton, 1983). Our own studies have shown that schistosomula survive for at least 96 h in different media (Basch,MEM,DMEM or TC 199) reported that schistosomula survive in Basch medium for several weeks (Abdulla et al 2009).…”
Section: S Mansoni In Vitro Assay Based On Schistosomulamentioning
confidence: 99%
“…For the isolation of cercarial bodies from tails, an ice-cold Hank's basal salt solution (HBSS) is added to the cercarial suspension and the tail-rich supernatant is decanted (Manneck et al 2009). Schistosomula are incubated in Basch medium (Basch, 1981) supplemented with serum and antibiotics or other culture media (Smyth and Halton, 1983). Our own studies have shown that schistosomula survive for at least 96 h in different media (Basch,MEM,DMEM or TC 199) reported that schistosomula survive in Basch medium for several weeks (Abdulla et al 2009).…”
Section: S Mansoni In Vitro Assay Based On Schistosomulamentioning
confidence: 99%
“…Cercarial tails were sheared off by 20 passes through 22G emulsifying needles after which schistosomule bodies were isolated free from tails by Percoll gradient centrifugation [19]. Schistosomula were washed 3 times in wash medium and cultured at 37°C under 5% CO 2 in air in modified Basch's medium [16] supplemented with small quantities of washed human erythrocytes. In some experiments, parasites were incubated in wash medium at 37° C under 5% CO 2 for 3 hours and recovered directly for electroporation.…”
Section: Parasitesmentioning
confidence: 99%
“…With the aim of establishing a more effective gene silencing, we employed electroporation procedures (as recommended [14]) to introduce dsRNA into cultured schistosomules. This developmental stage is readily maintained in vitro [16] and the life cycle can be subsequently re-established in vivo by needle passage into mice of schistosomules that have been genetically transformed in vitro [17]. This system is attractive and tractable for RNAi based investigation of gene function in S. mansoni [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Cercariae harvested from infected B. glabrata were used to infect C57BL/6 mice by subcutaneous injection (2,000 cercariae/mouse). Worms were perfused from mice 3 weeks postinfection (20) in Basch Schistosoma culture medium 169 (SCM) 3 with 10% fetal bovine serum instead of human serum (21) and complemented with 100 units/ml penicillin and 100 g/ml streptomycin. Worms were washed thoroughly and cultured in SCM at 37°C in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%